Transmission Dynamics of Clostridioides difficile in 2 High-Acuity Hospital Units. (29th January 2021) - Khader, Karim; Munoz-Price, L Silvia; Hanson, Ryan; Stevens, Vanessa; Keegan, Lindsay T; Thomas, Alun; Pezzin, Liliana E; Nattinger, Ann; Singh, Siddhartha; Samore, Matthew H
Abstract: Background: The key epidemiological drivers of Clostridioides difficile transmission are not well understood. We estimated epidemiological parameters to characterize variation in C. difficile transmission, while accounting for the imperfect nature of surveillance tests. Methods: We conducted a retrospective analysis of C. difficile surveillance tests for patients admitted to a bone marrow transplant (BMT) unit or a solid tumor unit (STU) in a 565-bed tertiary hospital. We constructed a transmission model for estimating key parameters, including admission prevalence, transmission rate, and duration of colonization to understand the potential variation in C. difficile dynamics between these 2 units. Results: A combined 2425 patients had 5491 admissions into 1 of the 2 units. A total of 3559 surveillance tests were collected from 1394 patients, with 11% of the surveillance tests being positive for C. difficile . We estimate that the transmission rate in the BMT unit was nearly 3-fold higher at 0.29 acquisitions per percentage colonized per 1000 days, compared to our estimate in the STU (0.10). Our model suggests that 20% of individuals admitted into either the STU or BMT unit were colonized with C. difficile at the time of admission. In contrast, the percentage of surveillance tests that were positive within 1 day of admission to either unit for C. difficile was 13.4%, with 15.4% in the STU and 11.6% in the BMT unit. Conclusions: Although prevalence was similar between the units, there were important differences in the rates of transmission and clearance. Influential factors may include antimicrobial exposure or other patient-care factors. Abstract : We used a dynamic transmission model to investigate the epidemiology of Clostridioides difficile in 2 high-acuity hospital units. We found consistent differences in rates of transmission and clearance between the 2 units across a range of surveillance sensitivity and specificity.